Growth Performance and Survival of African Catfish (Clarias Gariepinus) Fed on Different Diets - Aruho, Cassius; Ddungu, Richard; Mwanja, Mathew Tenywa; Immaculate, Kamahooro; Nkambo, Mujibu; Ondhoro, Constantine Chobet (International Journal of Fisheries and Aquatic Studies, 2017)
Two trial experiments were conducted to assess the performance of a commercial dry feed D in combination with de-capsulated Artemia (AD), Moina (FD) and dry feed alone on African catfish larvae Clarias gariepinus for 14 days. The trials were conducted sequentially, separated by two months at the same facility to validate the consistence of the weaning effect of the feed on the growth of catfish larvae. Results showed that the final larval mean total length TL (cm) of larvae weaned using a feed combination AD (Trial 1, 1.50±0.013 1; Trial 2, 1.44±0.011), significantly performed better in both trials than that of larvae weaned on the other two diets, FD (Trial1, 1.37±0.011; Trial 2, 1.3510±0.0091) and D (Trial 1, 1.39±0.0141; Trial 2, 1.3150±0.009). There was no significant difference in the final mean total length of catfish larvae weaned on feed combinations FD and D (P>0.05). Specific growth rate (daily length % increment) ranged between 4.2% and 5.1% in all trials with the highest noted in feed combination AD. Although, weaner feed combination AD performed better than other feeds, there were no significant differences in larval survival in all the trials (P>0.05). In spite of the good performance of the combination diet (AD), results from other feed (diet) combinations were fairly good as well. Feed D (57% crude protein CP) is an imported commercial feed that has been recently introduced in the country and can be popularized as a starter feed without the need to culture tedious live feeds or use of expensive Artemia combinations.
Keywords: African catfish; growth performance; Dry feed